LEGALISASI KAWIN BELUM TERCATAT (TINJAUAN TAFSIR GENDER) - Farichatul Maftuchah; Harisman (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This article examines the legalization of unregistered marriages in Indonesia through the lens of a filogynous gender hermeneutic, with particular attention to the structural vulnerabilities faced by women within a patriarchal legal system. Employing a qualitative methodology that integrates policy analysis and critical discourse approaches, the study draws on document analysis and semi-structured interviews conducted with three Gender Study Centers in Purwokerto. The findings reveal that, although Ministry of Home Affairs Regulation No. 108 of 2019 provides administrative recognition of unregistered marital status, it fails to ensure substantive legal protection for women. The filogynous gender hermeneutic is proposed as an alternative epistemological framework that challenges structural subordination and affirms female agency within marital relations. The article recommends policy reformulation, strengthened gender literacy, and inter-institutional collaboration as strategic measures to secure women’s rights in the context of legally unregistered marriages